1989
DOI: 10.1111/j.1365-2672.1989.tb02496.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of enzyme variation in Bacillus cereus and Bacillus thuringiensis

Abstract: Thirty-two strains of Bacillus spp. were examined in a multilocus enzyme study by agarose gel electrophoresis. The organisms were Bacillus thuringiensis (21 strains, B. cereus (8), including two of var. mycoides, and B. megaterium (3). Strains having similar enzyme variants were grouped into zymovars. A total of 10 of 11 enzyme loci studied were polymorphic and 27 zymovars were distinguished among the 32 strains. The results were subjected to numerical analysis, phenetic affinities and genetic distances betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…1 and 2). These findings resulted in several suggestions to consider B. cereus and B. thuringiensis (8,12,58), or these two bacteria together with B. anthracis (14,21), as one species. Results of our analysis of 16S and 23S rRNA sequences also show disagreement with the current tax- (Tables 2 and 3 and Fig.…”
Section: Vol 42 2004 Bacillus Cereus Group Classification 3725mentioning
confidence: 99%
“…1 and 2). These findings resulted in several suggestions to consider B. cereus and B. thuringiensis (8,12,58), or these two bacteria together with B. anthracis (14,21), as one species. Results of our analysis of 16S and 23S rRNA sequences also show disagreement with the current tax- (Tables 2 and 3 and Fig.…”
Section: Vol 42 2004 Bacillus Cereus Group Classification 3725mentioning
confidence: 99%
“…This may be a reflection of the narrow catchment area from which the strains were isolated and if we were to examine strain,$ from a wider geographical spread more variation may have been observed. However, the inclusion of thc reference strain suggests that this taxon is homogeneouQ; and this is supported by virtually identical whole-cell protein electrophoresis profiles (Kaji e t al., 1994 (Norris, 1964) and in a small study using multilocus enzyme electrophoresis two strains of serovar israelensis produced identical zymograms and of three strains of serovar kwstaki, two were identical and the third highly related (Zahner et al, 1989). Although most serovars were assigned to individual zymovars, strains of serovars finitimzls, entomocidzas and gallerim produced identical zymogram patterns, suggesting that they belong to the same clone.…”
Section: Correlation Of Ribotype With Serotypementioning
confidence: 97%
“…Classification into these species is based on pathogenicity (to mammals or insects), plasmid content, and gross morphological characteristics (11,13,34). The genetic similarity between the members of the B. cereus group has been extensively studied by means of various molecular methods, including multilocus enzyme electrophoresis (41), fluorescent amplified fragment length polymorphism analysis (24), and sequence analysis of 16S rRNA, 23S rRNA, gyrB, and a variety of housekeeping genes (6,9,28,32). The data generated by the bulk of these studies indicated that B. cereus and B. thuringiensis are virtually indistinguishable genotypically, which has led a number of researchers to suggest that these taxa may constitute a single species (6,8,9,23).…”
mentioning
confidence: 99%